(untitled) - B Chaitanya Deva (New Delhi, India, 1995)
Illustrated with over 80 drawings, the book is introduces to lay readers the basic concepts of India music to aid a fuller appreciation. Raga, its melodic base, is examined first, with scales and figures employed were necessary. Chapters on Tone and rythm follow. The many forms of composition - kheyal, thumri, kriti - are explained historically, and the lives of the masters briefly touched upon. Also discussed is the folk base of classical music - particularly the devotional forms that abound. Folk concert instruments of a wide range are described, and their canons of classification expounded
Keywords: music - india